(untitled) (Journal of actual problems of jurisprudence, 2018)
In recent years, almost in all countries of the CIS and Baltic bodies of constitutional control are institutionalized. These bodies are increasingly spreading their activities in the sphere of international law. Enhancing the role of the body of constitutional control in the implementation of the norms of international law is a relatively new phenomenon and very complex. In fact the body of constitutional control plays an important role in the development of legislation, and strengthening of cooperation between national and international legal systems. The Constitution, clearly prescribing issues of the Constitutional Council of the Republic of Kazakhstan, establishes the validity and the legal consequences of its final decisions. The resolution of issues, relating to the establishment and ensuring the relationship and the constitutional balance between national and international law, is included the sphere of the Constitutional Council. Key words: Constitution, the Constitutional Council, international law, national law.